Core Temperature Responses in Elite Cricket Players during Australian Summer Conditions - Sharon Stay; Michelle Cort; David Ward; Alex Kountouris; John Orchard; Justin Holland; Anna Saw (MDPI AG, 2018)
This study aimed to observe core temperature responses in elite cricket players under match conditions during the summer in Australia. Thirty-eight Australian male cricketers ingested capsule temperature sensors during six four-day first-class matches between February 2016 and March 2017. Core temperature (Tc) was recorded during breaks in play. Batters showed an increase in Tc related to time spent batting of approximately 1 °C per two hours of play (p < 0.001). Increases in rate of perceived exertion (RPE) in batters correlated with smaller elevations in Tc (0.2 °C per one unit of elevation in RPE) (p < 0.001). Significant, but clinically trivial, increases in Tc of batters were found related to the day of play, wet bulb globe temperature (WBGT), air temperature, and humidity. A trivial increase in Tc (p < 0.001) was associated with time in the field and RPE when fielding. There was no association between Tc and WBGT, air temperature, humidity, or day of play in fielders. This study demonstrates that batters have greater rises in Tc than other cricket participants, and may have an increased risk of exertional heat illness, despite exposure to similar environmental conditions.